Practical Implementation Strategies of Tartila Method for Improving Early Childhood’s Al Qur’an Reading Literacy - Widyawati, Ee; Nurhayati, Sri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the implementation of strategies to improve the ability to read and literacy of the Quran for early childhood through the tartiila method at the Early Childhood Tahfidz Education (TAUD) institution. This research uses qualitative descriptive method. The data collection techniques used in this study were interviews, observation and documentation. The research subjects in this study were 2 educators and 10 early childhood children at TAUD Roudhotul Qur'an Cimahi City. The data analysis technique used in this study is triangulation. Based on the results of the study, the implementation of learning strategies to improve literacy in reading the Quran in early childhood with the tartila method was carried out with the talaqy method, then with the approach of the function of letters or letter sounds (Thoriqotushautiyah) by learning to read Arabic letters directly snaring or marching. In addition, the Qur'an learning strategy with the tartila method is carried out with a sorogan system, emphasis on tone and recitation thus the educator brings an active and pleasant learning atmosphere. The use of this tartila method is proven to improve literacy in reading the Qur'an in early childhood. This study recommends that Qur'an teachers at the Early Childhood Tahfiz Institute can use this tartila method to improve Qur'an reading literacy in early childhood.